2003
DOI: 10.1007/s00221-002-1260-0
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of arm trajectory during continuous drawing movements in different dynamic environments

Abstract: Human subjects can readily adapt their movement trajectories to different dynamic or visuomotor environments. The focus of the current study was to determine whether subjects could simultaneously adapt to multiple dynamic environments. Subjects ( n=5) drew ellipses continuously for 70 s using a torquable manipulandum under six distinct dynamic conditions, representing the combination of load type (spring, viscous, and inertia) and load direction (assisting and opposing). Each subject performed two control, ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Various drawing tasks have been studied (Fukushi and Ashe, 2003;Lacquaniti, 1989;Mergl et al, 1999;Moran and Schwartz, 1999;Reina and Schwartz, 2003) and clinically, scoring the patient's drawing performance is a convenient and effective way to assess the severity of motor dysfunctions such as tremor of the upper limb (Bain et al, 1993). Digitising tablets can be used to quantify normal (Lacquaniti et al, 1987;Mergl et al, 1999) and tremulous arm movements (Elble et al, 1996;Erasmus et al, 2001;Pullman, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Various drawing tasks have been studied (Fukushi and Ashe, 2003;Lacquaniti, 1989;Mergl et al, 1999;Moran and Schwartz, 1999;Reina and Schwartz, 2003) and clinically, scoring the patient's drawing performance is a convenient and effective way to assess the severity of motor dysfunctions such as tremor of the upper limb (Bain et al, 1993). Digitising tablets can be used to quantify normal (Lacquaniti et al, 1987;Mergl et al, 1999) and tremulous arm movements (Elble et al, 1996;Erasmus et al, 2001;Pullman, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is well known that humans are capable of adapting to specific types of novel visuo-motor distortions (Held & Freedman, 1963; Ghahramani et al , 1996; Bock et al , 2003) or force field environments (Flash & Gurevich, 1991; Lackner & Dizio, 1994; Shadmehr & Mussa-Ivaldi, 1994). Also, it has been shown that humans can adapt to some types of perturbations more readily than others (Cunningham, 1989; Krakauer et al , 2000; Fukushi & Ashe, 2003; Hwang et al , 2003). If the decoded movement can be viewed as a distortion of the desired movement, then it may well be true that certain decoders may be more “learnable” than others.…”
Section: Introductionmentioning
confidence: 99%
“…38,32,48 For this reason, some motorized robots have been adapted to incorporate resistive brakes or challenge-based control algorithms to increase the difficulty of training or resist the user’s movements. 31,22,6,3,14,4 However, because these robotic devices use active actuators, they are typically expensive, bulky, and can even be potentially unsafe if not programmed correctly, which prevents them from being used in the comfort of a patients home. Thus, patients often rely on low-cost passive devices (e.g., elastic bands, weights, etc.…”
Section: Introductionmentioning
confidence: 99%